Answer:
false
Step-by-step explanation:
you first use distributive property for the multiplication
[(2*4x)-(2*11)]+9=19
8x-22+9=19
Then, you need to leave the variable alone moving all the other numbers with the opposite operation (addition to substraction, substraction to addition, multiplication to division, division to multiplication)
8x=19+22-9
8x=(19+22)-9
8x=41-9
8x=32
Then as 8 and x are multiplying you pass it dividing
x=32/8
x=4
Answer:
7
Step-by-step explanation:
Answer:
2.57 x 10^(-5)
Step-by-step explanation:
you have to move the comma sign in front of the first number considering 0 as a non-number.
Answer:
Step-by-step explanation:
x+(x+1)+(x+2)+(x+3)=-210
x+1x+1+1x+2+1x+3=-210
4x+6=-210
4x=-210-6
4x/4x=-216/4
x=54